Fostering Tolerance and Countering Extremism: Religious Moderation Efforts in Madrasah Aliyah Negeri Surabaya - Rohman, Fathur; Fahmi, Muhammad; Sucipto, Al Qudus Nofiandri Eko Dwi; Syaifuddin, Syaifuddin (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
This study examines the role of religious moderation as a preventive measure against radicalism, focusing on its implementation within the context of Madrasah Aliyah Negeri (MAN) Surabaya, under the initiatives of the Ministry of Religious Affairs. Using a descriptive qualitative approach, data were collected through participant observation, in-depth interviews, and document analysis. The research highlights how the religious moderation programs at MAN Surabaya, such as teacher training, religious tolerance discussions, and the integration of moderation values into both the curriculum and extracurricular activities, effectively reduce intolerance and increase student awareness of the importance of diversity and tolerance. These initiatives not only foster a more harmonious school environment but also strengthen students’ resilience to extremist ideologies by promoting a critical and inclusive understanding of religion. The study emphasizes the importance of integrating religious moderation in educational institutions as a long-term strategy to build societal resilience against radical ideologies. It further suggests that for sustained success, the active involvement of teachers, parents, and continuous program evaluation are crucial in maintaining the effectiveness of these initiatives.